Aligning the principles and practice of research integrity and research fairness in global health: a mixed-methods study - Sandra Alba; Rutuja Patil; Martijn Wienia; Masja Straetemans; Francis Kombe; Gowri Gopalakrishna; Harry Coleman; Nima Yaghmaei; Joseph Bukulu Sempa; Jake D Mathewson; Hannah Kabelka; Preeti Sohoni (BMJ Global Health)
Introduction In the past decade, global health research has seen a growing emphasis on research integrity and fairness. The concept of research integrity emerged in response to the reproducibility crisis in science during the late 2000s. Research fairness initiatives aim to enhance ownership and inclusivity in research involving partners with varying powers, decision-making roles and resource capacities, ultimately prioritising local health research needs. Despite extensive academic discussions, empirical data on these aspects, especially in the context of global health, remain limited.Methods To address this gap, we conducted a mixed-methods study focusing on research integrity and fairness. The study included an online frequency survey and in-depth key informant interviews with researchers from international research networks. The dual objectives were to quantify the frequency of practices related to research integrity and fairness and explore the determinants influencing these practices in global health.Results Out of 145 participants in the quantitative survey (8.4% response rate), findings indicate that global health researchers generally adhere to principles of research integrity and fairness, with variations in reported behaviours. The study identified structural, institutional and individual factors influencing these patterns, including donor landscape rigidity, institutional investments in relationship building, guidelines, mentoring and power differentials among researchers.Conclusion This research highlights that, despite some variations, there is a substantial alignment between research integrity and fairness, with both sharing similar determinants and the overarching goal of enhancing research quality and societal benefits. The study emphasises the potential to explicitly recognise and leverage these synergies, aligning both agendas to further advance global health research.